2004
DOI: 10.1074/jbc.m308668200
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Structure of Human OKL38 Gene and Its Differential Expression in Kidney Carcinogenesis

Abstract: We previously demonstrated the growth inhibitory property of OKL38 and its possible roles in mammary carcinogenesis. To further understand the regulation and roles of OKL38 in tumorigenesis we proceeded to clone and characterize the human OKL38 gene and three of its variants with transcripts of 1.9, 2.2, and 2.4 kb. The human OKL38 gene spans ϳ18 kb and contains 8 exons and 7 introns with exon size ranging from 92 to 1270 bp. RT-PCR and sequence analysis suggest that different transcripts were arrived through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 24 publications
8
38
0
Order By: Relevance
“…Conversely, Riou et al (2002) have reported the overexpression of OKL38 transcripts in HCC, even though the gene resided in chromosome 16q24, a region prone to loss of heterozygosity. Re-establishing the expression of HuOKL38-1a protein was shown to cause rounding and subsequently cell death of Chang liver cells, which was similar to our previous studies in kidney cancer (Ong et al, 2004a). Importantly, we have demonstrated that the 38 kDa isoform was more potent in inducing cell death compared to the 52 kDa isoform (Figure 3a).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Conversely, Riou et al (2002) have reported the overexpression of OKL38 transcripts in HCC, even though the gene resided in chromosome 16q24, a region prone to loss of heterozygosity. Re-establishing the expression of HuOKL38-1a protein was shown to cause rounding and subsequently cell death of Chang liver cells, which was similar to our previous studies in kidney cancer (Ong et al, 2004a). Importantly, we have demonstrated that the 38 kDa isoform was more potent in inducing cell death compared to the 52 kDa isoform (Figure 3a).…”
Section: Discussionsupporting
confidence: 88%
“…This observation was in agreement with our previous study in A498 kidney cancer cells (Ong et al, 2004a). Based on the above observations, we postulated that the discrepancy between mRNA and protein levels could be attributed to (i) mutation within the coding region leading to frame shift or change of amino-acid sequence, which resulted in the loss of protein expression or protein produced but not detected by anti-OKL38 antibody; and (ii) the involvement of the UTRs in translational regulation of OKL38 mRNA.…”
Section: The Orf Of Okl38 Was Intact In the Liver Cancer Cell Lines Asupporting
confidence: 94%
See 3 more Smart Citations